Investigating Smartphone Empowerment for Self-Regulated Learning in English Language Acquisition: A Descriptive Study - Rahmani, Eka Fajar (VELES Voices of English Language Education Society, 2024)
This study investigates the perceptions of undergraduate English Language Education students on the utilization of smartphones for self-regulated learning and the acquisition of the English language. The study investigates the ways in which smartphones facilitate the learning of English language through self-directed techniques, using Zimmerman's model of self-regulation and the MALL framework as theoretical basis. An exploratory investigation including 110 students was conducted to analyze their experiences, perspectives, and practices in utilizing language learning applications. The findings indicate a range of levels of knowledge and usage, with students generally acknowledging that smartphones are valuable tools for improving language acquisition through self-regulation. Analysis based on Zimmerman's model yields high average scores (3.42-3.51) for forethought, performance, and reflection & evaluation, indicating students engage in self-regulated learning practices. According to the MALL framework analysis, task design and design characteristics, all received high ratings (ranging from 3.42 to 3.68). This indicates that the app features effectively promote self-regulated learning activities. This study emphasizes the crucial role that smartphones play in promoting self-regulated learning practices and enhancing the acquisition of the English language among university students